Redefining Beijing Consensus: Ten general principles - Xin Li; Kjeld Erik Brødsgaard; Michael Jacobsen (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2009)
We argue, due to the conspicuous failure of Washington Consensus-guided reforms in most part of the developing world in 1990s and the outbreak of the current global financial crisis, Washington Consensus, as a general term of the neoliberal free market economic thinking, has been withering. In the meantime, Chinese economic model has gain wide recognition and praise worldwide. Joshua C. Ramo coined the term of Beijing Consensus as an alternative approach to economic development for developing nations. There has been hot debate on the notion of Beijing Consensus. We argue even though there are some problems in Ramo's original definition of Beijing Consensus, we should not reject this notion altogether. Instead, we should try to come up with better conceptualizations of this term. In this paper, we sum up ten general principles of the Chinese development model as our new definition of the Beijing Consensus.
hdl:10398/7830
Keywords: 330; Washington consensus; Beijing consensus; China; Development model; Economic reform; Wirtschaftsreform; Wirtschaftspolitik; Entwicklungsstrategie; China; Entwicklungsländer